A fluorescence biosensor for Salmonella typhimurium detection in food based on the nano-self-assembly of alendronic acid modified upconversion and gold nanoparticles. Issue 21 (17th May 2021) - Chen, Min; Pan, Leiqing; Tu, Kang
Abstract : A simple and quick-response fluorescent biosensor for Salmonella typhimurium detection based on the recognition of an aptamer coupled with alendronic acid (ADA)@upconversion nanoparticles (UCNPs) and gold nanoparticles (AuNPs) has been developed. Abstract : A simple and quick-response fluorescent biosensor for Salmonella typhimurium detection based on the recognition of an aptamer coupled with alendronic acid (ADA)@upconversion nanoparticles (UCNPs) and gold nanoparticles (AuNPs) has been developed. Briefly, the aptamer can adsorb on the surfaces of the AuNPs via a "Au–S" bond to protect the AuNPs from aggregation in highly concentrated salt solution. Then, the AuNPs and UCNPs are linked by electrostatic adsorption, which leads to a decrease in the fluorescence peak at 541 nm based on fluorescence resonance energy transfer (FRET) between the UCNPs and AuNPs. In the presence of Salmonella typhimurium, the "Au–S" bond was broken, and the fluorescence intensity at 541 nm was recovered. Under optimal conditions, the correlation between the concentration of S. typhimurium and the intensity of the fluorescent biosensor signals was observed to be linear within the range of 1.16 × 10 2 to 1.16 × 10 7 CFU mL −1 ( R 2 = 0.9912), and the detection limit of the developed biosensor was observed to be 36 CFU mL −1 . Furthermore, the proposed method was successfully used to detect the Salmonella typhimurium pathogen in food samples with satisfactory results.